2006
DOI: 10.1093/nar/gkl339
|View full text |Cite
|
Sign up to set email alerts
|

High potency silencing by single-stranded boranophosphate siRNA

Abstract: In RNA interference (RNAi), double-stranded short interfering RNA (ds-siRNA) inhibits expression from complementary mRNAs. Recently, it was demonstrated that short, single-stranded antisense RNA (ss-siRNA) can also induce RNAi. While ss-siRNA may offer several advantages in both clinical and research applications, its overall poor activity compared with ds-siRNA has prevented its widespread use. In contrast to the poor gene silencing activity of native ss-siRNA, we found that the silencing activity of boranoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
87
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 41 publications
0
87
0
4
Order By: Relevance
“…siRNA shorter than canonical siRNA could also induce efficient silencing of target genes in mammalian cells acting via RNAi mechanism [87][88][89][90]. Short siRNAs have some benefits as inducers of RNAi such as reduction of immune response and decreased cost of the synthesis [76].…”
Section: Short Noncanonical Rnamentioning
confidence: 99%
See 4 more Smart Citations
“…siRNA shorter than canonical siRNA could also induce efficient silencing of target genes in mammalian cells acting via RNAi mechanism [87][88][89][90]. Short siRNAs have some benefits as inducers of RNAi such as reduction of immune response and decreased cost of the synthesis [76].…”
Section: Short Noncanonical Rnamentioning
confidence: 99%
“…Early studies demonstrated that 5′-phosohorylated antisense siRNAs with 22-40 nt in length were able to induce gene silencing in Caenorhabditis elegans [92,93]. Several studies investigated the possibility of using antisense strand of siRNA 19-29 nt in length for transient knockdown of target genes in mammalian cells [88][89][90]. Antisense siRNA entered the RISC complex and provided mRNA cleavage but with lower efficiency in comparison with canonical siRNA.…”
Section: Short Noncanonical Rnamentioning
confidence: 99%
See 3 more Smart Citations